Reshaping CAR-T cells through overexpression of T cell factor 1 - Yao, Hao; Ding, Yuntian; Chen, Qian; Han, Huixiu; Sedloev, David; Müller-Tidow, Carsten; Sauer, Tim; Schmitt, Anita; Schmitt, Michael; Wang, Lei (Frontiers in Immunology, 2025)
IntroductionAlthough chimeric antigen receptor (CAR) T cell therapy has revolutionized treatment for hematologic malignancies, insufficient CAR-T cell persistence remains a major limitation. T cell factor 1 (TCF-1) is a transcription factor crucial for T cell development, self-renewal, and memory formation. However, CAR-T cells typically exhibit low TCF-1 expression. This study investigated whether restoring TCF-1 expression could enhance CAR-T cell persistence and functionality.MethodsHuman peripheral blood T cells were transduced with third-generation CD19 or CD33 CAR retroviral vectors, with or without a TCF-1 (Tcf7.NGFR) construct. Phenotypic, functional, and transcriptional analyses were performed using flow cytometry, cytokine profiling, long-term killing assays, and RNA sequencing. Data mining and machine learning were applied for high-dimensional immunophenotyping.ResultsTCF-1 overexpression generated CAR-T cells with reduced apoptosis, lower activation marker expression, and an increased proportion of naïve and stem cell–like subsets. These modified cells displayed a higher CD4⁺/CD8⁺ ratio, preserved proliferative capacity, and maintained cytotoxicity with attenuated cytokine release. Long-term co-culture assays demonstrated superior persistence and sustained tumor-killing activity in TCF-1–overexpressing CAR-T cells. Transcriptomic profiling revealed downregulation of apoptotic and cytokine release pathways, and enrichment of cell cycle and metabolic pathways supporting T cell longevity.DiscussionOverexpression of TCF-1 confers resistance to apoptosis, limits excessive activation, and promotes a less differentiated phenotype, collectively enhancing CAR-T cell persistence and long-term efficacy. These findings suggest that TCF-1 modulation represents a promising strategy to improve durability and safety of CAR-T cell therapy in relapsed or refractory hematologic malignancies.